From Benign Beginning to Malignant Giant: The Journey of Recurrent Cystosarcoma Phyllodes - Dinesh Kumar; Md Sahil Reza; Sushovon Das; Utpal De (National Board of Examinations Journal of Medical Sciences)
A 42-year-old lady presented with a recurrent left breast mass, initially diagnosed as a benign phyllodes tumor. Despite wide local excision, the tumor recurred thrice over three years, each recurrence demonstrating increasing stromal cellularity and atypia. Imaging revealed a giant heterogeneous mass, and core biopsy confirmed a borderline phyllodes tumor. Surgical management included a wide local excision of the mass and chest wall with immediate reconstruction. Histopathology showed malignant transformation with negative margins. Postoperative recovery was uneventful. This case highlights the aggressive potential of recurrent phyllodes tumor and emphasizes the importance of close monitoring, timely surgical intervention, and consideration of adjuvant therapy.